The Effect of Soaking Jambal Siam Fish (Pangasianodon hypophthalmus) In Pineapple Peel (Ananas comosus) Solution On Leukocyte Image - Herparinda Novita; Morina Riauwaty; Henni Syawal (Jurnal Akuakultur SEBATIN, 2023)
This research was carried out in July 2021 – September 2021 at the Laboratory of Parasites and Fish Diseases. This study aims to obtain the best dose of pineapple peel solution. This study used a Complete Randomized Design (RAL) consisting of 5 treatments and 3 tests. The treatment in this study was that there was an influence where the best treatment was found in P2 (Soaking of pineapple skin solution dose 1,800 ppm tested challenged with A. hydrophila bacteria) with an average total leukocytes of 9.92 x 104 cells / mm3, total lymphocytes 82.67%, total monocytes 9.33%, neutrophy value 8.00% phagocytic value 37.00%, siamese jambal fish dilution classified as good with a value of 93.33%, and water quality during the study temperatures ranged from 27.3–29oC,, pH 6.3–6.6, DO 3.4–4.2 mg/L, and NH3 0.01-0.02 mg/L.